BRAZILIAN NAVY ACTIVITIES IN ANTARCTICA. - Jesus, Dennis Teixeira de; Souza, Haynnee Trad (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2017)
The Brazilian Antarctic Program celebrates, in 2007, his 25th anniversary. During these 25 years of activities in Antarctica, the Brazilian Navy has being responsible for providing the necessary conditions for the execution of scientific research in that continent. In this paper we related the logistics involved on installations maintenance, equipments acquisition and epair, training of personnel and environmental protection procedures to guarantee the Brazilian permanence in that inhospitable region. O Programa Antártico Brasileiro comemora, em 2007, seu Jubileu de Prata. Durante esses 25 anos de atividades na Antártica, a Marinha do Brasil foi a responsável por prover as condições necessárias para a realização de pesquisas científicas naquele continente. Aqui apresentamos a logística que envolve a manutenção das instalações, aquisição e reparo de equipamentos, treinamento e preservação ambiental que garantem a permanência brasileira naquela região tão inóspita.